A virus isolation from rinderpest suspected calves - Feridun Öztürk; Sibel Yavru; Atilla Şimşek; Hüdaverdi Erer (Eurasian Journal of Veterinary Sciences)
A highly fethal disease, suspected of, resembling Rinderpest, was diagnosed as a result of elinical and pathological examinations, in calves, in october 1991. in Konya. Total of 9 specimens, including 2 mesenteriallymph nodes, 2 spleens, 2 buffy coat samples and 3 nasal swaps was obtained for virology testing from Rinderpest suspected calves. The inoculation of specimens to Foetal Calf Kidney (FCK) cell cultures, showed that, 4 of the specimens of the 2 mesenterial lymph nodes and 2 nasal swaps was positive for cytopathologic effect (CPE). The histopathologic examination of specimens with CPE in cell cultures, revealed intrastoplasmic and intranuclear inclusion bodies.